Separating nanobubble nucleation for transfer-resistance-free electrocatalysis - Shasha Guo; Maolin Yu; Jinn-Kye Lee; Mengyi Qiu; Dundong Yuan; Zhili Hu; Chao Zhu; Yao Wu; Zude Shi; Wei Ma; Shuangyin Wang; Yongmin He; et al. (Nature Communications)
Abstract Electrocatalytic gas-evolving reactions often result in bubble-covered surfaces, impeding the mass transfer to active sites. Such an issue will be worsened in practical high-current-density conditions and can cause sudden cell failure. Herein, we develop an on-chip microcell-based total-internal-reflection-fluorescence-microscopy to enable operando imaging of bubbles at sub-50 nm and dynamic probing of their nucleation during hydrogen evolution reaction. Using platinum-interfacial metal layer-graphene as model systems, we demonstrate that the strong binding energy between interfacial metal layer and graphene—evidenced by a reduced metal-support distance and enhanced charge transfer—facilitates hydrogen spillover from platinum to the graphene support due to lower energy barriers compared to the platinum-graphene system. This results in the spatial separation of bubble nucleation from the platinum surface, notably enhancing catalytic activity, as demonstrated in both microcell and polymer electrolyte membrane cell experiments. Our findings offer insights into bubble nucleation control and the design of electrocatalytic interfaces with minimized transfer resistance.